Stability and visual outcomes of the capsulotomy-fixated FEMTIS-IOL after automated femtosecond laser-assisted anterior capsulotomy - Auffarth, Gerd U.; Friedmann, Elfriede; Breyer, Detlef; Kaymak, Hakan; Holland, Detlef; Dick, Burkhard; Petzold, Alexander; Shah, Sunil; Ladaria, Luis Salva; Garcia, Scott Anderson; Khoramnia, Ramin (American journal of ophthalmology, 2021)
Purpose - To evaluate stability and performance of a new monofocal anterior capsulotomy-fixated intraocular lens (IOL) (FEMTIS; Teleon Surgical B.V., Spankeren, Netherlands) after femtosecond laser-assisted cataract surgery (FLACS). - Design - Prospective, multicenter, interventional, noncomparative case series. - Methods - FLACS with FEMTIS IOL was performed in 336 eyes of 183 cataract patients with fixation of the IOL to the anterior capsulotomy followed up for 12 months. Examination included uncorrected distance visual acuity (UDVA), best-corrected visual acuity (CDVA), subjective refraction, IOL centration, posterior capsule opacification (PCO), and investigators' satisfaction questionnaire. - Results - At 12 months, mean IOL rotation was 1.50 ± 1.76 degrees and decentration 0.14 ± 0.14 mm from baseline (day of surgery). Mean horizontal IOL tilt was 0.70 ± 0.60 degrees and vertical 1.15 ± 1.06 degrees relative to the baseline (crystalline lens). Mean distance between IOL and iris was 0.32 mm to 0.36 mm for all measured meridians. Mean UDVA was 0.12 ± 0.14 logMAR (range -0.20 to 0.54 logMAR), mean CDVA -0.01 ± 0.09 logMAR (range -0.30 to 0.20 logMAR). Mean spherical equivalent was 0.35 ± 0.53 diopter (D) and 98% of eyes (n = 235) were within ±1.0 D. Median PCO score was 1 with an Nd:YAG laser rate of 3.1% after 12 months. Most surgeons were very satisfied (median score: 1) with surgery and implanted IOL. - Conclusions - Implantation of FEMTIS IOL provided excellent visual and stable refractive outcomes. IOL decentration was very low compared to other published studies and showed an exceptional high in-the-bag stability over a 12-month period. This lens benefits from femtosecond laser capsulotomies. It can be positioned very predictably and offers an optimal platform for toric and multifocal IOL optics.
Available online 4 January 2021
Gesehen am 17.08.2021